STANDARISASI RESEP KUE BAY TAT - Ulya, Wafiqah; Fridayati, Lucy; Elida, Elida; Gusnita, Wiwik (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Bay Tat cake is a traditional food typical of the Serawai Tribe in Semidang Alas Maras District, Seluma Regency, which does not yet have a standard recipe. This study aims to standardize ingredients, manufacturing techniques, and evaluate the quality of Bay Tat cake in terms of shape, color, aroma, texture, and taste. This study used a mixed method approach. Qualitative data were obtained through interviews, observations, and documentation of 10 informants who make Bay Tat, while quantitative data were collected through organoleptic tests of several recipes. Five initial recipes were selected to three, then retested until the best recipe was obtained based on panelist assessments. The results showed that the best recipe used standardized ingredient measurements, consistent processing techniques, and produced Bay Tat quality that is round like a flower, yellow-brown in color, has a distinctive aroma of coconut milk and brown sugar, a soft texture, and a sweet-savory taste. This study produced a standard recipe that can be used as a reference in the preservation and development of local culinary specialties of Serawai.Keywords: Recipe Standardization, Bay Tat Cake, Serawai Tribe, Processing Techniques, Organoleptic Quality.